Network Pharmacology-Based Analysis of Pogostemon cablin (Blanco) Benth Beneficial Effects to Alleviate Nonalcoholic Fatty Liver Disease in Mice - Cui, Yizhe; Wang, Qiuju; Chang, Renxu; Aboragah, Ahmad; Loor, Juan J.; Xu, Chuang (Frontiers in Pharmacology, 2021)
Non-alcoholic fatty liver disease (NAFLD) is the most common cause of chronic liver disease and is associated with high morbidity and mortality. Pogostemon Cablin (Blanco) Benth, Huo Xiang (HX) is a perennial herb with unique antioxidant and anti-inflammatory properties, and thus, it can positively affect liver function. In this study, network pharmacology and pharmacological experiments were used to predict and validate the potential effects of HX on liver function in NAFLD and its underlying mechanisms. Network pharmacology showed that nine components were identified, which interacted with 82 NAFLD-related targets, revealing four target genes, TNF, IL-6, TP53, and AKT1. HX prevents the development and progression of NAFLD through different pathways and targets, and quercetin-regulated lipid metabolism, anti-inflammatory, and antioxidant pathways play an essential role in the treatment of NAFLD role. HX significantly attenuated lipid accumulation in vivo and in vitro compared to fed HFD. The reduction of lipid accumulation in hepatocytes induced by high doses of HX was partly due to the downregulation of SREBF1 and FASN abundance. Validation experiments were then performed, which showed that HX inhibited the activation of NF-κB/IκB signaling and reduced the release and levels of pro-inflammatory factors (TNF-α and IL-6). The data suggest that HX can attenuate abnormal lipid metabolic responses and enhance antioxidant mechanisms. Thus, plants used in traditional Chinese medicine can achieve pharmacological effects through a multi-level response.